1999
DOI: 10.1681/asn.v103594
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine Plasma Concentrations Differ in Patients with End-Stage Renal Disease

Abstract: Abstract. Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of endothelial nitric oxide (NO) synthase. Its concentration is elevated in patients with end-stage renal disease (ESRD), in part because it is excreted via the kidneys. In this study, the plasma concentrations of ADMA, symmetric dimethylarginine, and L-arginine were determined in relation to plasma nitrate levels (as an index of NO formation) for a group of 80 patients with ESRD. The effects of two treatment methods, i.e., hemodialysis (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(11 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Another trial on preclinical models discovered a link between SDMA levels and creatinine clearance. Kielstein et al reported that SDMA levels increased by more than 400% when relative to our data (27). On the other hand, Leone et al, reported a similar (up to four-fold) increase in the construction of both ADMA and SDMA, however, their study was limited to following up only 15 volunteers (6 controls and 9 hemodialysis patients) (23).…”
Section: Discussioncontrasting
confidence: 50%
“…Another trial on preclinical models discovered a link between SDMA levels and creatinine clearance. Kielstein et al reported that SDMA levels increased by more than 400% when relative to our data (27). On the other hand, Leone et al, reported a similar (up to four-fold) increase in the construction of both ADMA and SDMA, however, their study was limited to following up only 15 volunteers (6 controls and 9 hemodialysis patients) (23).…”
Section: Discussioncontrasting
confidence: 50%
“…Although not statistically significant, the serum glutamate levels showed a tendency to increase after HD in our study (removal rate: −28.5%; Figure 2 ). In addition, it has been reported that the plasma ADMA concentration increased 1 h after HD compared to before HD, and decreased significantly 5 h after HD compared to 1 h after HD [ 30 ]. The authors speculated that the increase in the ADMA levels after HD could be partly the result of a redistribution of tissue ADMA into the plasma compartment during HD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that the plasma ADMA concentration increased 1 h after HD compared to before HD, and decreased significantly 5 h after HD compared to 1 h after HD [ 30 ]. The authors speculated that the increase in the ADMA levels after HD could be partly the result of a redistribution of tissue ADMA into the plasma compartment during HD [ 30 ]. Similarly, there could be a possibility that the distribution from the tissue into the serum compartment during HD affected the removal rates analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported to be elevated in CKD ( Leone et al, 1992 ; Fleck et al, 2001 ) and ESRD patients on dialysis ( Anderstam et al, 1997 ). Interestingly, ADMA levels have been found to correlate with the severity of atherosclerosis ( Kielstein et al, 1999 ), CV events, and mortality in CKD patients ( Zoccali et al, 2001 ), and even with renal disease state progression ( Fliser et al, 2005 ). Asymmetric dimethylarginine levels can be influenced by Ang II through the activation of AT 1 receptors; thus, Ang II can indirectly predispose to further NOS inhibition ( Palm et al, 2007 ), perpetuating to eNOS uncoupling with free radicals generation ( Vallance and Leiper, 2004 ).…”
Section: Pathogenesis Of Hypertension In Chronic Kidney Diseasementioning
confidence: 99%